Hand-held volatilome analyzer based on elastically deformable nanofibers - Yucel, Muge (2019)
This study reports on a hand-held volatilome analyzer for selective determination of clinically relevant biomarkers in exhaled breath. The sensing platform is based on electrospun polymer nanofiber-multiwalled carbon nanotube (MWCNT) sensing microchannels. Polymer nanofibers of poly(vinylidene fluoride) (PVDF), polystyrene (PS), and poly(methyl methacrylate) (PMMA) incorporated with MWCNT exhibits a stable response to interferences of humidity and CO2 and provides selective deformations upon exposure of exhaled breath target volatilomes acetone and toluene, exhibiting correlation to diabetes and lung cancer, respectively. The sensing microchannels “P1” (PVDF-MWCNT), “P2” (PS-MWCNT), and “P3” (PMMA-MWCNT) are integrated with a microfluidic cartridge (μ-card) that facilitates collection and concentration of exhaled breath. The volatilome analyzer consists of a conductivity monitoring unit, signal conditioning circuitries and a low energy display module. A combinatorial operation algorithm was developed for analyzing normalized resistivity changes of the sensing microchannels upon exposure to breath in the concentration ranges between 35 ppb and 3.0 ppm for acetone and 1 ppb and 10 ppm for toluene. Subsequently, responses of volatilomes from individuals in the different risk groups of diabetes were evaluated for validation of the proposed methodology. We foresee that proposed methodology provides an avenue for rapid detection of volatilomes thereby enabling point of care diagnosis in high-risk group individuals.